Cross-sector partnership and human services in Australian states and territories: Reflections on a mutable relationship. Issue 2 (1st June 2014) - Butcher, John; Dalton, Bronwen
Abstract: Under Australia's federal system subnational governments fund the delivery of a wide range of public services. In particular, state and territory governments have increasingly looked to the non-profit sector to deliver human services under contract. Over time, the contracting regimes employed by public sector commissioners have taken on more 'relational' characteristics, accompanied by a gradual softening of public sector resistance to non-profit sector input into policy development. Nevertheless, the Australian non-profit sector is fragmented and, although policy capacity within the sector has undoubtedly matured, it is also unevenly distributed. Almost two decades of contracting has left its mark on organisational culture. There are fears within the non-profit sector that it is organisations with the largest 'market share' that gain a seat at the policy table.